2019
DOI: 10.1007/s11356-019-04134-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of tear lipid composition in two human populations with different exposure to particulate matter in La Plata, Argentina

Abstract: To identify the changes in the lipid profile of the tear film in two human populations exposed to different levels of particulate material, and its relationship with dry eye, by gas chromatography with mass spectrometry (GC-MS) detection. A panel study involving 78 volunteers, who live and work in two locations in Argentina with different pollution levels: urban zone (n = 44) and industrial zone (n = 34). We measured the mean levels of particulate matter (PM) exposure. The tear samples were analyze by gas GC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, the TFLL properties are dictated by its lipid composition (e.g., the types of lipids, saturation content, ratio of the short-to long-chain fatty acids), and this is demonstrated by the varying properties of different TFLL models (especially with the incorporation of free fatty acids) 104 . Changes in the TFLL composition induced by air pollution are predictable, and these patterns can differentiate air pollution exposure groups 105 . Gas chromatography mass spectrometry analysis of fatty acid concentrations in the tear uid of volunteers have reveled associations between air pollution and the fatty acid pro le of the tear uid 105 .…”
Section: Biological Markers Of Exposure In the Tear Fluidmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the TFLL properties are dictated by its lipid composition (e.g., the types of lipids, saturation content, ratio of the short-to long-chain fatty acids), and this is demonstrated by the varying properties of different TFLL models (especially with the incorporation of free fatty acids) 104 . Changes in the TFLL composition induced by air pollution are predictable, and these patterns can differentiate air pollution exposure groups 105 . Gas chromatography mass spectrometry analysis of fatty acid concentrations in the tear uid of volunteers have reveled associations between air pollution and the fatty acid pro le of the tear uid 105 .…”
Section: Biological Markers Of Exposure In the Tear Fluidmentioning
confidence: 99%
“…Changes in the TFLL composition induced by air pollution are predictable, and these patterns can differentiate air pollution exposure groups 105 . Gas chromatography mass spectrometry analysis of fatty acid concentrations in the tear uid of volunteers have reveled associations between air pollution and the fatty acid pro le of the tear uid 105 . Speci cally, people living in an urban (low-pollution) location exhibited a signi cant difference in the concentration of 15 fatty acids compared to volunteers from an industrial (high-pollution) location (p < 0.05) 105 .…”
Section: Biological Markers Of Exposure In the Tear Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravimetry was used to determine the particle content in each sample. PM collection was carried out simultaneously in both areas following the methodology of (Gutierrez et al 2019).…”
Section: Particulate Matter Collectionmentioning
confidence: 99%
“…From another aspect, the ocular surface is directly exposed to the outside environment, thereby making tear composition incredibly sensitive to external environmental changes. One recent study reported significant differences in tear lipid composition in two human populations with different exposure to particulate matter in urban and industrial zones [ 6 ], which can be valuable in characterizing environmental pollution and its impact on disease. In addition, tear chemical composition is sensitive to internal emotional and psychological states.…”
mentioning
confidence: 99%